CRYPTOCURRENCY AS MONEY: Islamic Monetary System Perspective - Luhur Prasetiyo; Unun Roudlotul Janah (IAIN Ponorogo, 2022)
The existence of cryptocurrencies that have emerged and developed since the last decade is still a debate, both in terms of function, regulation and compliance with Islamic economic principles. Different countries give different attitudes towards cryptocurrencies. Some countries accept its existence, while some other countries reject it. This is inseparable from the question that arises whether cryptocurrencies function as money or commodities. In addition, the absence of an official institution that is responsible for and regulates the circulation of cryptocurrencies and no underlying assets is also another problem. This article aims to see how cryptocurrencies are positioned based on their nature, characteristics and functions using an Islamic finance point of view. The results of the study indicate that cryptocurrencies currently carry out more functions as a store of value that are not in accordance with the Islamic financial system. In addition, the use of cryptocurrencies as money and means of payment carries a fairly large risk. This violates the principle of property protection in the maqasid al-shari'ah view.